Competency‐based education: programme design and challenges to implementation. Issue 5 (May 2016) - Gruppen, Larry D; Burkhardt, John C; Fitzgerald, James T; Funnell, Martha; Haftel, Hilary M; Lypson, Monica L; Mullan, Patricia B; Santen, Sally A; Sheets, Kent J; Stalburg, Caren M; Vasquez, John A
Abstract : Context: Competency‐based education (CBE) has been widely cited as an educational framework for medical students and residents, and provides a framework for designing educational programmes that reflect four critical features: a focus on outcomes, an emphasis on abilities, a reduction of emphasis on time‐based training, and promotion of learner centredness. Each of these features has implications and potential challenges for implementing CBE. Methods: As an experiment in CBE programme design and implementation, the University of Michigan Master of Health Professions Education (UM‐MHPE) degree programme was examined for lessons to be learned when putting CBE into practice. The UM‐MHPE identifies 12 educational competencies and 20 educational entrustable professional activities (EPAs) that serve as the vehicle for both learning and assessment. The programme also defines distinct roles of faculty members as assessors, mentors and subject‐matter experts focused on highly individualised learning plans adapted to each learner. Conclusions: Early experience with implementing the UM‐MHPE indicates that EPAs and competencies can provide a viable alternative to traditional courses and a vehicle for rigorous assessment. A high level of individualisation is feasible but carries with it significant costs and makes intentional community building essential. Most significantly, abandoning a time‐based framework is a difficult innovation to implement in a university structure that is predicated on time‐based education. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.